Combination of Ashwagandha Water Extract and Intermittent Fasting as a Therapy to Overcome Cisplatin Resistance in Breast Cancer: An in vitro and in vivo Study - Jawarneh, Sajidah; Talib, Wamidh H. (Frontiers in Nutrition, 2022)
Breast cancer is considered a universal public health dilemma in women. Due to high toxicity and low selectivity of conventional anticancer therapies, there is a growing trend of using plant-derived natural products in cancer prevention and therapy. Ashwagandha (Withania somnifera, WS) has been used in the Mediterranean region and Ayurvedic medicine for millennia as a functional food and a medicinal plant with anticancer activity. Besides, intermittent fasting (IF) has been engaged recently in cancer treatment. Hence, the combination of WS and IF provides possible solutions to treat cancer and reduce chemoresistance, when combined with chemotherapy. In this study, WS root (WSR), IF and cisplatin were tested on cisplatin-sensitive (EMT-6/P) and cisplatin-resistant (EMT-6/C) mouse mammary cell lines. The phytochemical content of WSR extract was analyzed using LC-MS analysis. Antiproliferative and apoptotic effects were assessed for WSR extract, cisplatin, and their combination in vitro using MTT and caspase-3 assays. In vivo study was used to assess the effect of WSR extract, IF, cisplatin, and their combinations in mice inculcated with EMT-6/P and EMT-6/C cells. The safety profile was also investigated using liver enzymes and creatinine assays. In vitro, WSR extract and cisplatin had a synergistic effect in both cell lines. The same combination induced apoptotic effect higher than single treatments in both cell lines. In vivo, several combinations of WSR extract, IF or cisplatin caused significant tumor size reduction and improved cure rate in mice implanted with EMT-6/P and EMT-6/C cell lines. IF-treated groups showed a significant reduction in serum glucose and an elevation in β-hydroxybutyrate (BHB) levels. In the safety profile, WSR extract, IF and their combinations were safe. Overall, the combination of WSR extract and IF provides a promising solution for breast cancer treatment besides cisplatin by reducing the proliferation of cancer cells through induction of apoptosis. Moreover, they minimize the toxicity of cisplatin to the liver and kidney.